2017
DOI: 10.1177/1010428317705333
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-1826 in plasma correlates with circulating tumor cells and is a prognostic marker in colorectal cancer

Abstract: Our previous study showed that miR-1826 was a newly identified oncogenic non-coding RNA in colorectal cancer. But the potential relationship between miR-1826 and tumor metastasis has not been fully elucidated. The purpose of this study was to evaluate the clinical significance of circulating miR-1826 and its possible associations with circulating tumor cells in colorectal cancer. Our results first found that serum miR-1826 was significantly upregulated in colorectal cancer patients, compared with that in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Xue et al focused on the role of miR-638 in OS progression and demonstrated that miR-638 could enhance OS cell apoptosis and inhibit cell proliferation and invasion [22]. miR-1826 has been studied in some human cancers, such as melanoma [14], colorectal carcinoma [13], renal cancer [15], and bladder cancer [23]. The expression patterns of miR-1826 present a contradictory situation that the increased miR-1826 expression was found in colorectal carcinoma, while the decreased miR-1826 expression was observed in melanoma, renal cancer, and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xue et al focused on the role of miR-638 in OS progression and demonstrated that miR-638 could enhance OS cell apoptosis and inhibit cell proliferation and invasion [22]. miR-1826 has been studied in some human cancers, such as melanoma [14], colorectal carcinoma [13], renal cancer [15], and bladder cancer [23]. The expression patterns of miR-1826 present a contradictory situation that the increased miR-1826 expression was found in colorectal carcinoma, while the decreased miR-1826 expression was observed in melanoma, renal cancer, and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that miR-191-5p was upregulated in OS tissues and associated with poor prognosis of OS patients [27]. For miR-1826, its aberrant expression has also been described as an indicator for the overall survival of colorectal carcinoma [13] and renal cancer [15]. According to the survival analysis in this study, the OS patients with low miR-1826 expression had a shorter survival time, and the downregulation of miR-1826 was determined as an independent prognostic indicator for the overall survival in OS patients, indicating that miR-1826 might serve as a novel biomarker for the prognosis of OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation